Israel’s efforts to improve status in the international system through the Abraham accords - Syafaat, Zahirah Wishal Prijasy (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
This study examines and explains how Israel's efforts to improve its status as a developing country in the Middle East and the international system through the Abraham Accords. The Abraham Accords is an agreement that is an attempt to normalize Israel's relations with the United Arab Emirates and Bahrain. The Abraham Accords opened up new opportunities for Israel, which is a new player and a developing country, to become a bigger and more important player in the Middle East. This research uses two theories, namely Defensive Neorealism Theory and Liberal Theory to support the explanations in this research, and uses a qualitative method with a descriptive approach to further understand how Israel and other Arab countries, such as the United Arab Emirates and Bahrain are trying to improve their status in the international system through the framework of this agreement. Through the idea of emerging economies and also how a country can raise its status profile in the international system, it can be seen that the Abraham Accords is one of Israel's ways to strengthen its status in the international system through its role as one of the developing countries. The Abraham Accords is also a way for Israel to put aside the issue of conflict between Israel and Palestine.